2010
DOI: 10.1590/s0102-76382010000300004
|View full text |Cite
|
Sign up to set email alerts
|

Implante transapical de valva aórtica: resultados de uma nova prótese brasileira

Abstract: Objective: The aortic valve replacement is a routine procedure with acceptable risk, but in some cases, such a risk can justify contraindication. The minimally invasive transcatheter aortic valve implantation has been viable, with lower morbidity and mortality. The aim of this study was to develop a national catheter-mounted aortic bioprosthesis for the aortic position implant.Methods: After animal studies, 14 patients with high EuroSCORE underwent transcatheter aortic valve implantation. Median Logistic EuroS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 26 publications
1
23
0
4
Order By: Relevance
“…Transthoracic defibrillation pads were placed in the left, anterior and posterior thoracic region. 6. CPB was set up in a conventional manner, testing the vacuum system through a negative pressure gauge connected to the oxygenator venous reservoir.…”
Section: Methodsmentioning
confidence: 99%
“…Transthoracic defibrillation pads were placed in the left, anterior and posterior thoracic region. 6. CPB was set up in a conventional manner, testing the vacuum system through a negative pressure gauge connected to the oxygenator venous reservoir.…”
Section: Methodsmentioning
confidence: 99%
“…In our environment Gaia et al 6 reported a 30-day mortality found in 18.18% and overall mortality (42.42%) mainly attributed to infectious complications postoperatively. The fact that 39.39% of these patients underwent surgery in the presence of decomposition and prolonged hospitalization, induces a greater risk of colonization and infection.…”
Section: Discussionmentioning
confidence: 66%
“…Aiming precisely or very elderly patients with high surgical risk, there has been the alternative of percutaneous aortic bioprosthesis method feasible, safe and highly effective in this subgroup of patients [23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%